The action of red scorpion (Mesobuthus tamulus coconsis, pocock) venom and its isolated protein fractions on blood sodium levels - Badhe,R. V. (2007)
Red scorpion (Mesobuthus tamulus or Buthus tamulus) venom samples were collected at different regions of India: western (Chiplun and Ahmednagar from Maharashtra State) and southern (Ratnagiri and Chennai from Tamil Nadu State). The action of whole venoms on the blood sodium levels of mice was assessed using flame photometry. Seven peptides were common to all venom samples. They were separated using the native polyacrylamide gel electrophoresis (PAGE) technique and their activities were also studied using flame photometry. There was a decrease in the concentration of sodium ions in the serum, which suggested the blockage of such ions by scorpion venom toxins. Among the 10 protein bands isolated, the band at 79.6 kDa presented maximum activity in decreasing serum sodium ions concentration. Whole venom from Chiplun region also showed maximum activity. The western blotting technique demonstrated that the anti-scorpion venom sera produced by Haffkine Biopharmaceuticals Corporation Ltd., India, neutralized all four venom samples.